Peran Kompetensi Kepribadian Kepala Sekolah sebagai Teladan Perilaku Guru di SMP Islam Terpadu Ibnu Halim: The Role of the Principal's Personality Competence as a Role Model for Teacher Behavior at Ibnu Halim Integrated Islamic Middle School - Sylvi Marsella Diastami; Tengku Darmansah (ITScience (Information Technology and Science), 2025)
This study uses a descriptive qualitative research method to analyze the role of the principal's personality competency as a role model for teacher behavior in improving school quality. As an educational leader, the principal is required to possess five core competencies: personality, managerial, entrepreneurial, supervisory, and social competencies. Among these five competencies, personality competency plays a crucial role because it encompasses noble character, integrity, openness, self-control, and leadership interests and talents. This competency serves as the foundation for creating a positive, harmonious, and conducive school environment for all members of the school community. This research was conducted at Ibnu Halim Integrated Islamic Junior High School, Medan Deli, through observation, interviews, and documentation. The results indicate that principals who possess and consistently apply personality competency are able to serve as role models, mentors, and sources of inspiration and motivation for teachers. The impact is seen in the teachers' increased work ethic, discipline, and sense of responsibility in carrying out their duties. However, several obstacles remain, such as differences in perception, lack of professionalism, and resistance to change. To overcome these challenges, the principal implemented strategies such as shared perceptions, effective communication, instilling commitment, religious and community activities, providing rewards and sanctions, and participating in training. Thus, the principal's personality competency contributes significantly to shaping teachers' professional behavior and improving the quality of education in schools. The conclusions drawn from the research conducted indicate that principals with strong personality competency can create a school climate that not only focuses on academics but also fosters strong character development and professional synergy among educators.